Building Low-Code Applications with Mendix: Discover best practices and expert techniques to simplify enterprise web development - Kenneweg, Bryan; Kasam, Imran; McMullen, Micah (Packt Publishing, 2021)
Transform your app ideas into fully functional prototypes with the help of expert tips and best practices from Mendix partners Key Features Meet the ever-increasing demand for software solution delivery without having to write any codeBuild high-availability, low-cost applications unlike those developed via a traditional software engineering approachExplore Mendix from product design through to delivery using real-world scenarios Book Description Low-code is a visual approach to application development. It enables developers of varying experience levels to create web and mobile apps using drag-and-drop components and model-driven logic through a graphic user interface. Mendix is among the fastest-growing platforms that enable low-code enthusiasts to put their software ideas into practice without having to write much code, and Building Low-Code Applications with Mendix will help you get up and running with the process using examples and practice projects. The book starts with an introduction to Mendix, along with the reasons for using this platform and its tools for creating your first app. As you progress, you’ll explore Mendix Studio Pro, the visual environment that will help you learn Mendix app creation. Once you have your working app ready, you’ll understand how to enhance it with custom business logic and rules. Next, you’ll find out how to defend your app against bad data, troubleshoot and debug it, and finally, connect it with real-world business platforms. You’ll build practical skills as the book is filled with examples, real-world scenarios, and explanations of the tools needed to help you build low-code apps successfully. By the end of this book, you’ll have understood the concept of low-code development, learned how to use Mendix effectively, and developed a working app. What you will learn Gain a clear understanding of what low-code development is and the factors driving its adoptionBecome familiar with the various features of Mendix for rapid application developmentDiscover concrete use cases of Studio ProBuild a fully functioning web application that meets your business requirementsGet to grips with Mendix fundamentals to prepare for the Mendix certification examUnderstand the key concepts of app development such as data management, APIs, troubleshooting, and debugging Who this book is for This book is for tech-savvy business analysts and citizen developers who want to get started with Mendix for rapid mobile and web application development. The book is also helpful for seasoned developers looking to learn a new tool/platform and for anyone passionate about designing technical solutions without wanting to indulge in the complexities of writing code. The book assumes beginner-level knowledge of object-oriented programming and the ability to translate technical solutions from business requirements.